2017
DOI: 10.4102/sajce.v7i1.481
|View full text |Cite
|
Sign up to set email alerts
|

The patterns and prevalence of monosyllabic three-letter-word spelling errors made by South African English First Additional Language learners

Abstract: There is growing evidence of systematic underachievement of South African primary school learners in reading in English as the first additional language. There is a small but growing literature that provides insights, that is, causes, patterns and prevalence, into this phenomenon. Through a secondary analysis of a spelling component of a literacy test that was administered as an end-line assessment for a randomised control trial, this article provides new evidence for and insight into the patterns and prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…If one were to simplify it, spelling is understood as a process of encoding, in which spoken words are converted into written symbols (Mpiti 2012). Studies on spelling have centred around three central topics (Fleisch et al 2017). The first deals with the developmental stages of spelling, the second the relationship between spelling and reading and the last, to a lesser extent, the linguistic categories and analysis of spelling errors (Fleisch et al 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…If one were to simplify it, spelling is understood as a process of encoding, in which spoken words are converted into written symbols (Mpiti 2012). Studies on spelling have centred around three central topics (Fleisch et al 2017). The first deals with the developmental stages of spelling, the second the relationship between spelling and reading and the last, to a lesser extent, the linguistic categories and analysis of spelling errors (Fleisch et al 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies on spelling have centred around three central topics (Fleisch et al 2017). The first deals with the developmental stages of spelling, the second the relationship between spelling and reading and the last, to a lesser extent, the linguistic categories and analysis of spelling errors (Fleisch et al 2017). These topics have been explored predominately in English, with few studies focusing on African languages (Alcock & Ngorosho 2003, 2007De Sousa, Greenop & Fry 2011;Diemer, van der Merwe & de Vos 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…• In quantitative research, information about the reliability index of test instruments was not always reported. In 'The patterns and prevalence of monosyllabic three-letterword spelling errors made by South African First Additional Language learners', Fleisch et al (2017) provide a level of detail that should be made available to readers of research articles.…”
Section: Failure To Provide a Detailed Audit Trailmentioning
confidence: 99%
“…A related question is what causes lack of access to bottom-up decoding and encoding strategies? A study of the patterns and prevalence of monosyllabic three-letter-word spelling errors made by English FAL learners (Fleisch, Pather, & Motilal, 2017) brought to light misspellings of vowels in monosyllabic words and a high prevalence of errors which the researchers classified as pre-grapho-phonemic. Results showed that over two thirds of Grade 4 learners in the sample had not mastered the spelling of words benchmarked for Grade 2 learners.…”
Section: Literacymentioning
confidence: 99%